PROGRAM PELATIHAN GURU DALAM PEMBUATAN DAN IMPLEMENTASI MEDIA CERITA BERGAMBAR PADA ANAK USIA DINI DI PUSAT KERJA GURU (PKG) KECAMATAN SEMPARUK - Eliyah Eliyah; Asyruni Multahada; Astaman Astaman (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2022)
This Community Service Activity (PKM) aims to provide training for early childhood Islamic education (PAUD) teachers in creating and implementing illustrated story media for early childhood at the Teacher Work Center in Semparuk District. The training will be held on July 29, 2021, from 10.00 WIB to 14.30 WIB. The activity begins with a pre-test, which is testing the insights of the training participants regarding learning media. After that, it was continued by giving short material from the three speakers, namely Mrs. Eliyah, Mrs. Asyruni and Mr. Astaman. The next event is the practice of making picture story media. Finally, the participants who were previously made into groups, presented (practiced) the results of the practice of making the illustrated media. The results of the training show that in general PAUD teachers are able to make storytelling media with pictures very well. However, there are still shortcomings that must be improved such as in terms of language style that is less attractive to students, slightly stiff body gestures, poor intonation and articulation, and the stories chosen must be more contextual for early childhood children.